The Tradition of Duduk Senden Among Postpartum Mothers: A Phenomenological Study in Rejosari Village, Kalidawir District, Tulungagung - Nurosidah Sayyidatuz (IJCRE - International Journal of Culture, Religion, and Education, 2025)
The tradition of caring for mothers after giving birth is still widely found in society. As is the case in Java, postnatal care habits are believed to come from generation to generation. This belief has implications from a medical and philosophical perspective, which includes the desire to understand events wisely and wisely. This research attempts to examine the tradition of duduk senden for mothers after giving birth and its philosophical meaning. The type of research used in this research is phenomenology with ethnographic methods. The results of the research show 1) The practice of duduk senden begins with reading toyyibah and shalawat sentences, the senden position is carried out by sitting half asleep with pillows stacked as support for the mother's back and the legs together. 2) The philosophical meaning of duduk senden contains the meaning of monotheism (faith), the meaning of ethics and manners, and the meaning of protecting the body and soul.